The impacts of lasting occupation : lessons from Israeli society - Bar-Tal, Daniel; Shnell, Itzhak (New York : Oxford University Press, 2013)
'The Impacts of Lasting Occupation' examines the effects that Israel's decades-long occupation of Palestinian territories have had on Israeli society. The consequences of occupation are evident in all aspects of Israeli life, including its political social, legal, economic, cultural, and psychological spheres.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Israel-Arab War, 1967 -- Occupied territories; Arab-Israeli conflict -- 1993-; Israel -- Social conditions -- 21st century